Simple Tool of Metabolomic Studies: TLC-Based Metabolite Profiling Peronema canescens Jack in Archipelago Indonesia - Nurfijrin Ramadhani; Endang Lukitaningsih; Abdul Rohman; Arief Nurrochmad (Majalah Obat Tradisional, 2025)
Peronema canescens Jack is a species of tropical plant utilized for its empirical applications, such as an antipyretic, antimalarial, immune stimulant, cold medicine, and mouthwash for its antiseptic properties. The objective of this study was to identify differences in the metabolite composition of P. canescens Jack leaves at different geographical locations. The metabolite profile was examined by thin-layer chromatography densitometry. The samples were collected from 10 distinct locations at varying elevations, with each location being sourced from three separate plants. Fingerprint metabolomics employs chemometric techniques such as Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA). The PCA analysis resulted in PC1 value of 41% and PC2 value of 32.6%, and these findings indicate the importance of considering the geographical locations where leaves are collected, as they reveal regional differences in the metabolism of P. canescens Jack secondary metabolites. Hierarchical cluster analysis (HCA) classified P. canescens Jack into four distinct clusters based on the closeness of their metabolite profiles. TLC is useful for the quality control of P. canescens Jack leaves based on variation geographical and authentication.